Did the charcoal-based iron industry really drive the forest cover decline in the Northern Pyrenees?. (June 2022) - Fouédjeu, Léonel; Burri, Sylvain; Saulnier, Mélanie; Larrieu, Laurent; Paradis-Grenouillet, Sandrine; Py-Saragaglia, Vanessa
Abstract: Through a reconstruction of the chronology and intensity of charcoal-making activities, this paper re-opens the debate about the supposed impact of the charcoal iron industry on forest cover in the French Pyrenees. This reappraisal focuses on the former territory of the communities of Haut-Vicdessos valley. This more refined chronology, based on the analyses of historical documents (n = 617) and charcoal kiln remains (n = 42), has highlighted the non-linear industrial development. The emergence of water-powered bloomeries during the early 14th c. led to a brief expansion of the iron industry, but was followed by a slowdown in the 15th c. The combined effect of regulation and the outsourcing of a part of the charcoal supply on other territories, mitigated the impact of the iron industry on local forest, avoiding a forest crisis. The most significant industrial growth occurred from the mid-17th c. with development of the Catalan bloomery. Forests underwent major changes in structure and composition but cover was maintained to satisfy the local economy and people's needs. Charcoal production always occurred in well-stocked forests dominated by beech and fir. The increase of charcoal supply combined to the agro-pastoral growth led to the prohibition of charcoal-making in the mid-18th c. and to the exclusive recourse to an external fuel supply. Minimum forest cover was only reached in the mid-19th c. due to the demographic explosion resulting in the increase of daily needs and in the refocus on agro-pastoral economy. Conversely to the common premise, the iron charcoal industry in European mountains did not necessarily induce forest depletion but rather its maintenance through sustainable management and policies. Highlights: We revisited the chronology and intensity of the charcoal iron industry in Vicdessos. The spread of water-powered bloomeries did not lead to a 14th c. forest crisis. The iron industry's real impulse occurred in the 17th c. with the Catalan bloomery. Local communities preserved woodland cover through efficient management. The iron industry was not a major driver of the mid-19th c. forest-cover minimum.